Dialing up Critical Feminist Research as Lockdown Dialed us Down: How a Pandemic Sparked Community Food Dialogs in Cape Town, South Africa - Paganini, Nicole; Ben-Zeev, Keren; Bokolo, Khutala; Buthelezi, Nomonde; Nyaba, Sanelisiwe; Swanby, Haidee (Frontiers in Sustainable Food Systems, 2021)
The COVID-19 pandemic and its control measures had a devastating impact on household food security in South Africa. The pandemic brought existing food injustice patterns, such as spatial inequality, intersectionality, and the causes of food poverty to the forefront, especially for women. It also galvanized momentum in the people's agenda for solidarity and stimulated community members' calls for an overhaul of the existing commercialized food system toward hyper-localized, community-led solutions such as food dialogs and community kitchens. First and foremost, that meant talking about hunger and addressing its root causes. This paper reports on a co-research process on household food security during the pandemic in four neighborhoods of the Cape Flats. This study found that household food insecurity and the roles women play in food systems are significantly shaped by intersectionality: the consequences of being women, Black or Persons of Color, residents of geographies of social and economic marginalization within the city, and historically excluded from higher education. In this paper, we provide reflections on the co-research process from the perspectives of co-researchers, the project coordinator, and the project funder by applying a critical feminist framework and by answering the question: How can critical feminist research steer community-led action? Community members from the Cape Flats and five post-graduate students from a Berlin-based institute conceptualized this study and it was implemented by community researchers and projects partners in 2020. The paper highlights important aspects of the methodology, particularly the joint contextualization and sense making of findings by community researchers who placed food insecurity results in the context of their lived experiences. Based on their discussions, the co-researchers created visions for post-COVID-19 food environments, one of which is discussed in this paper: destigmatization of hunger. Hunger was described by co-researchers as a problem hidden by individuals and silenced by communities.